P3.162 Developing a clinical prediction rule to target sti testing and contraception to women in community settings: implications for sexual health surveys. (8th July 2017) - Edelman, Natalie; Ro, De Visser; Cm, Mercer; Cassell, J
Abstract : Introduction: Applied sexual health surveys investigate associations between psychosocial and demographic factors, sexual risk behaviour, uptake of interventions and sexual morbidity. This work improves clinical and public health understandings of sexual morbidity but may not be easily translated into practice. We seek to identify key features of research surveys that would make them more relevant to the development and use of risk assessment and targeting tools. Methods: To support the development of clinically-embedded risk assessment tools we undertook a systematic review of population surveys reporting on sexual risk and morbidity. We identified aspects of sexual health research questionnaire items and their reporting which could be adapted to better serve public health and clinical services to identify patients for targeted intervention. Results: Four key deficiencies were identified: 1.The degree to which sexual risk behaviours such as multiple partnerships and inconsistent contraception use predict adverse outcomes remains under-investigated; 2.Surveys frequently use composite measures with complex scoring systems; 3. Analyses often fail to report on non-response to individual items and the prevalence of exposures; 4. Sexual risk behaviours and morbidity are often reported without measures of absolute risk. Conclusion: There is a strategic need to exploit survey research better in order to embed investigation of risk factors in clinical risk prediction tools. Survey analyses should investigate which sexual risk behaviours warrant different sexual health interventions, and use measures of absolute risk. Researchers should favour questionnaire items that are concise and easy to score, and should report on item non-response and prevalence of exposures. These steps would facilitate the development of brief, acceptable and adequately predictive tools.